Age-specific mortality rate ratios in adolescents and youth aged 10–24 years living with perinatally versus nonperinatally acquired HIV. (15th March 2021) - Desmonde, Sophie; Ciaranello, Andrea L.; Malateste, Karen; Musick, Beverly; Patten, Gabriela; Vu, An Thien; Edmonds, Andrew; Neilan, Anne M.; Duda, Stephany N.; Wools-Kaloustian, Kara; Davies, Mary-Ann; Leroy, Valériane
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To measure mortality incidence rates and incidence rate ratios (IRR) in adolescents and youth living with perinatally acquired HIV (YPHIV) compared with those living with nonperinatally acquired HIV (YNPHIV), by region, by sex, and during the ages of 10–14, 15–19, and 20–24 years in IeDEA. Design and methods: All those with a confirmed HIV diagnosis, antiretroviral therapy (ART)-naive at enrollment, and who have post-ART follow-up while aged 10–24 years between 2004 and 2016 were included. We estimated post-ART mortality incidence rates and 95% confidence intervals (95% CI) per 100 person-years for YPHIV (enrolled into care <10 years of age) and YNPHIV (enrolled ≥10 years and <25 years). We estimate mortality IRRs in a negative binomial regression model, adjusted for sex, region time-varying age, CD4 + cell count at ART initiation (<350 cells/μl, ≥350 cells/μl, unknown), and time on ART (<12 and ≥12 months). Results: Overall, 104 846 adolescents and youth were included: 21 340 (20%) YPHIV (50% women) and 83 506 YNPHIV (80% women). Overall mortality incidence ratios were higher among YNPHIV (incidence ratio: 2.3/100 person-years; 95% CI: 2.2–2.4) compared with YPHIV (incidence ratio: 0.7/100 person-years; 95% CI: 0.7–0.8). Among adolescents aged 10–19 years, mortality was lower among YPHIV compared with YNPHIV (all IRRs <1, ranging from 0.26, 95% CI: 0.13–0.49 in 10–14-year-old boys in the Asia-Pacific to 0.51, 95% CI: 0.30–0.87 in 15–19-year-old boys in West Africa). Conclusion: We report substantial amount of deaths occurring during adolescence. Mortality was significantly higher among YNPHIV compared to YPHIV. Specific interventions including HIV testing and early engagement in care are urgently needed to improve survival among YNPHIV.